DYADIC ESSAY TECHNIQUE IN IMPROVING THE STUDENTS EXPLANATION TEXT - Radiah Akbar (Universitas Negeri Makassar, 2021)
Explanation text is one of genre texts that is learnt and needed to be mastered by SMA students. Dyadic Essay Technique was ere considered useful to increase the students’ skills in writing explanation text. This study implemented classroom action research and the subject of this research was class XI MIPA 1 SMAN 2 Maros, which consisted of 32 students. The study was focused on examining the students in improving content and organization in writing explanation text. The improvement of the students’ achievement in writing content and organization was shown by the students’ scores in D-test (50 and 55.7), Cycle I (60.3 and 60), and Cycle II (81.1 and 71.). Hopefully, the result of this research is able to be replicated by SMA teachers and students in solving similar problems faced in writing explanation text. Keywords: Dyadic Essay Technique, Writing, Explanation Text